The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1103/physrevb.70.195215
|View full text |Cite
|
Sign up to set email alerts
|

Double-exchange mechanisms for Mn-doped III-V ferromagnetic semiconductors

Abstract: A microscopic model of indirect exchange interaction between transition metal impurities in dilute magnetic semiconductors (DMS) is proposed. The hybridization of the impurity delectrons with the heavy hole band states is largely responsible for the transfer of electrons between the impurities, whereas Hund rule for the electron occupation of the impurity d-shells makes the transfer spin selective. The model is applied to such systems as n−type GaN:Mn and p−type (Ga,Mn)As, p−type (Ga,Mn)P. In n−type DMS with M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 76 publications
3
60
0
Order By: Relevance
“…The double-exchange model is based on a physical picture of the d electron hopping between atoms with strong on-site exchange. 34 In the present study of ZnO:Gd nanowires, V O donates two electrons to the system, mediating the ferromagnetic exchange and hence, the s-f coupling is more prominent than other mechanisms. 34,35 According to our calculations, introducing V Zn does not increase the ferromagnetic coupling energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The double-exchange model is based on a physical picture of the d electron hopping between atoms with strong on-site exchange. 34 In the present study of ZnO:Gd nanowires, V O donates two electrons to the system, mediating the ferromagnetic exchange and hence, the s-f coupling is more prominent than other mechanisms. 34,35 According to our calculations, introducing V Zn does not increase the ferromagnetic coupling energy.…”
Section: Resultsmentioning
confidence: 99%
“…34 In the present study of ZnO:Gd nanowires, V O donates two electrons to the system, mediating the ferromagnetic exchange and hence, the s-f coupling is more prominent than other mechanisms. 34,35 According to our calculations, introducing V Zn does not increase the ferromagnetic coupling energy. Moreover, p-f exchange interaction mediated by holes is not possible, as the calculated DOS of Gd-doped ZnO nanowire shows a shift of Fermi level towards the conduction band, implying that electrons can mediate FM through s-f interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and generally accepted for the shallow acceptor counterparts to GaAs:Mn, applies well to the intermediate extrinsic GaAs:Mn. The perception of merged impurity and valence bands in highly Mn-doped metallic GaAs is now also firmly established in the microscopic theory community 7,15,[18][19][20][21][22] and provides a qualitative, and often a semiquantitative, description of micromagnetic and magnetotransport characteristics of bulk and microstructured ͑Ga,Mn͒As ferromagnets. 6,7,15 Our paper, which we believe further establishes the valence-band nature of the Fermi level states in metallic GaAs:Mn, is timely as the topic is still not fully settled.…”
Section: 11mentioning
confidence: 99%
“…In Ref. 19 it is shown that doubleexchange and superexchange mechanisms can play an important role on the static polarization of a DMS. According to these considerations the present work is addressed to the study of the third-order exchange contributions and its influence on the time evolution of the total magnetization in a DMS.…”
Section: B Equations Of Motionmentioning
confidence: 99%